Morphological and molecular characterization of Stenocranus pacificus (Hemiptera: Delphacidae) on maize plants - Anivea Fachmi; Dita Megasari; Ramadhani Mahendra Kusuma (Jurnal Ilmiah Pertanian)
Maize (Zea mays L.) is one of the primary food commodities with a strategic role in improving Indonesia's economy. Additionally, maize contributes to food diversification and security. One of the main threats to maize production is pest attacks, including Stenocranus pacificus and Peregrinus maidis. This study aims to identify S. pacificus (Hemiptera: Delphacidae) found on maize crops in three sub-districts of Lamongan Regency, East Java, using both morphological and molecular approaches. Morphological identification revealed that the planthopper found is S. pacificus, characterized by an orange abdomen in male imagos and a white abdomen in female imagos. Molecular testing through polymerase chain reaction (PCR) using mitochondrial Cytochrome Oxidase I deoxyribonucleic acid (mtCOI DNA) showed that the S. pacificus from Lamongan is 99.53% similar to S. pacificus WRJJ_UNILA and WRJB_UNILA. These findings are expected to support more accurate, rapid, and effective pest control strategies.